2023
DOI: 10.1039/d2lc00573e
|View full text |Cite
|
Sign up to set email alerts
|

A review on microrobots driven by optical and magnetic fields

Abstract: This review covers the working mechanisms, recent progress and state-of-the-art applications of microrobots driven by optical and magnetic fields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 178 publications
0
28
0
Order By: Relevance
“…Compared with other strategies for steering micromotors, such as those using magnetic fields, physical boundaries, or taxis, optoelectronic steering is dynamic and reprogrammable and capable of manipulating single micromotors or their collectives. Moreover, because dielectrophoresis and the optoelectronic effect are universal, micromotors of a wide variety of propulsion mechanisms or physiochemical properties can be steered with high precision and tunability.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with other strategies for steering micromotors, such as those using magnetic fields, physical boundaries, or taxis, optoelectronic steering is dynamic and reprogrammable and capable of manipulating single micromotors or their collectives. Moreover, because dielectrophoresis and the optoelectronic effect are universal, micromotors of a wide variety of propulsion mechanisms or physiochemical properties can be steered with high precision and tunability.…”
Section: Discussionmentioning
confidence: 99%
“…Today, the development of microrobots is a highly dynamic field of research [ 1 , 2 , 3 ]. There are numerous different approaches presented in scientific literature [ 4 , 5 ]: magnetic swimmers [ 6 , 7 ] and inchworms [ 8 ], optical driven microrobots [ 9 , 10 ], lyposome-based systems [ 11 ], enzyme catalysis powered micromotors [ 12 ], and many others. Among them, microorganisms are also a focus of interest because microbial cells are already mobile systems with high levels of autonomy as they have already an “energy system”, can use chemicals from the environment as food, use chemical or sunlight as an energy source, replicate itself via division, provide the biosynthesis of necessary chemicals, and demonstrate directional movement.…”
Section: Introductionmentioning
confidence: 99%
“…28 Similar studies have been widely reported that micromotors are advantageous for biomedical applications. 29,30 Nevertheless, on the path of micromotors toward practical applications, many obstacles that need to be urgently addressed have been proposed, such as the limited capacity of individual micromotors 31 and the scalability of functionality. 32…”
Section: Introductionmentioning
confidence: 99%
“…28 Similar studies have been widely reported that micromotors are advantageous for biomedical applications. 29,30 Nevertheless, on the path of micromotors toward practical applications, many obstacles that need to be urgently addressed have been proposed, such as the limited capacity of individual micromotors 31 and the scalability of functionality. 32 Inspired by the behaviours of creatures in nature, many studies on collective behaviours or transformations between different behaviours of micromotors have been reported recently and have aroused wide interest.…”
Section: Introductionmentioning
confidence: 99%